2022
DOI: 10.1155/2022/8733598
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lianhua Qingke Tablets in the Treatment of Mild and Common-Type COVID-19: A Randomized, Controlled, Multicenter Clinical Study

Abstract: Background. Lianhua Qingke (LH) tablets is an effective traditional Chinese medicine against various viral infections, especially in relieving coughing. However, its effects on COVID-19 are unknown. Methods. To examine the therapeutic effectiveness of LH tablets in COVID-19 patients with mild and common types, a randomized, multicenter, controlled study was carried out. COVID-19 cases were randomized to undergo routine treatment with or without LH tablets (4 tablets, three times a day) for 14 days. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…LHQK has been recommended for acute tracheobronchitis, cough, expectoration with a dry throat, and chest distress. Previous studies have proved the therapeutic effects of LHQK on ALI induced by bacteria and smoking exposure, and pneumonia caused by HCoVs (HCoV‐229E and SARS‐CoV‐2) in an animal model and human patients 23‐26,64,65 . Clinical studies shown the effects of LHQK on relieving cough and expectoration in symptomatic COVID‐19 cases 25,64,65 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…LHQK has been recommended for acute tracheobronchitis, cough, expectoration with a dry throat, and chest distress. Previous studies have proved the therapeutic effects of LHQK on ALI induced by bacteria and smoking exposure, and pneumonia caused by HCoVs (HCoV‐229E and SARS‐CoV‐2) in an animal model and human patients 23‐26,64,65 . Clinical studies shown the effects of LHQK on relieving cough and expectoration in symptomatic COVID‐19 cases 25,64,65 .…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the assessment of lung pathology also revealed that LHQK effectively attenuated LPS-induced alveolar septum thickening, alveolar-space broadening, and alveolar wall destruction (Figure 1n-p). immunomodulatory capacities of LHQK, 25,53 we wonder whether LHQK has an impact on LPS-induced lung inflammation. To address this question, we evaluated the concentration of total protein, the protein level of Mucin protein (Muc5AC), and the concentration of proinflammatory cytokines (IL-6, TNF-α, and IL-1β) in plasma and BALF of mice.…”
Section: Lhqk Attenuated Lps-induced Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and clinical evidence has demonstrated the therapeutic effects of LHQK in reducing sputum production 23 and viscosity. 24 In addition, LHQK has been proven to be effective in promoting sputum expulsion in both animal models and patients. 25 This study investigated the therapeutic effects and underlying mechanisms of LHQK in a rat model of AECOPD induced by cigarette smoke (CS) exposure and lipopolysaccharide (LPS) intratracheal instillation.…”
Section: Introductionmentioning
confidence: 99%
“…There were 22 studies published in Chinese(Ai X. Y. et al, 2020; Jin W. et al, 2020; Zhang C. T. et al, 2020;AI et al, 2020b; Yu P. et al, 2020;Wang Y. L. et al, 2020;Ding et al, 2020;Duan et al, 2020;Fu et al, 2020;Lin et al, 2020;Sun et al, 2020; Hu F. et al, 2021; Wang L. Q. et al, 2021;He et al, 2021;Li et al, 2021;Ping et al, 2021;Qiu et al, 2021;Sun S et al, 2021;Wu et al, 2021;Yan et al, 2021) (2 registered prospectively(Jin W. et al, 2020;Sun Y et al, 2021)) and 13 published in English which were all registered(Xiao M. Z. et al, 2020; Wang J. B. et al, 2020;Xiong et al, 2020; Liu J. et al, 2021;An et al, 2021; Hu K. et al, 2021; Zhang X. Y. et al, 2021;Ma et al, 2021;Ni et al, 2021;Xu et al, 2021;Zeng et al, 2021;Zhao et al, 2021;Zhang et al, 2022). Twenty-four OBs(Chen et al, 2020a; Frontiers in Pharmacology frontiersin.org…”
mentioning
confidence: 99%